1985
DOI: 10.1085/jgp.85.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP inhibits Na+/H+ exchange at the apical membrane of Necturus gallbladder epithelium.

Abstract: The effects of elevating intracellular cAMP levels on Na' transport across the apical membrane of Necturus gallbladder epithelium were studied by intracellular and extracellular microelectrode techniques . Intracellular cAMP was raised by serosal addition of the phosphodiesterase inhibitor theophylline (3 mM) or mucosal addition of either 8-Br-cAMP (1 mM) or the adenylate cyclase activator forskolin (10 pM). During elevation of intracellular cAMP, intracellular Na' activity (aNai) and intracellular pH (pHi) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 28 publications
3
43
0
Order By: Relevance
“…However, this was never the case in the present study: i.e., the cytosol pH was usually raised by db-cAMP (Table 6). Similarly, REUSS and PETERSEN (1985) found that in gallbladder epithelium of Necturus, the intracellular pH was elevated for the first 2 min but lowered by about 0.1 pH with theophylline application for several minutes. Although they explained that pH elevation was not due to cAMP, but to the effect of the drug entry of theophylline (pKa = 8.8), our data showed that cytosol alkalosis was induced without theophylline application.…”
Section: Discussionmentioning
confidence: 72%
“…However, this was never the case in the present study: i.e., the cytosol pH was usually raised by db-cAMP (Table 6). Similarly, REUSS and PETERSEN (1985) found that in gallbladder epithelium of Necturus, the intracellular pH was elevated for the first 2 min but lowered by about 0.1 pH with theophylline application for several minutes. Although they explained that pH elevation was not due to cAMP, but to the effect of the drug entry of theophylline (pKa = 8.8), our data showed that cytosol alkalosis was induced without theophylline application.…”
Section: Discussionmentioning
confidence: 72%
“…Necturus gallbladder (33). However, whether cAMP inhibits apical Na'-H' exchange in the medullary thick ascending limb has not been determined.…”
Section: Resultsmentioning
confidence: 99%
“…Maximal doses of 8-bromo-CAMP, of the phosphodiesterase inhibitor theophylline, or of the adenylate cyclase activator forskolin inhibited Na'/H' exchange by~50% . The effect involved a decrease in the V.,, of the exchanger (Reuss and Petersen, 1985).…”
Section: Introductionmentioning
confidence: 99%